(untitled) (BIMRAD Journal, 2026)
Saint Martin’s Island (SMI) is the southern-most island of Bangladesh with unique coral ecosystem. The island is a vital outpost for various maritime activities in the Bay of Bengal and due to the evolving geo-strategic & environmental dynamics, the importance as well as vulnerability of this island has increased significantly. SMI is connected to the mainland only via sea and therefore, ensuring safe & efficient navigational route is imperative. To ensure sustained communication with SMI, BN Survey Team conducted hydrographic survey and proposed two routes: a permanent northward navigational route from SMI to BN Inani Jetty or BIWTA Nuniachara Jetty and an alternative eastward navigational route from SMI to Shahporir Dwip Jetty. The proposed alternative navigational route was immediately inaugurated, but the northward navigational route is yet to make headway due to numerous challenges of seaward transportation and loading/unloading. Under prevailing circumstances, failing to ensure uninterrupted communication with SMI will not only ensure the failure of island-based economic and environmental activities, but may threaten the suppy chain and as a consequence, the very existence of Bangladesh’s unique coral-bearing island. Amid evolving geo-strategic & environmental dynamics, this paper highlights the hydrographic challenges related to safe & efficient navigational route for sustenance of SMI. BIMRAD Journal VOLUME 6, ISSUE 1, DEC 2025; PP-48-63